Composite material for heat management of new energy battery and preparation method of composite material
By using composite materials of paraffin, boron nitride, expanded graphite and multi-layer graphene in thermal management of new energy batteries, the problems of low thermal conductivity and uneven temperature in the existing technology are solved, and more efficient thermal management is achieved and extended battery life.
Patent Information
- Application Number
- CN202411686535.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing phase change material cooling systems have problems such as high weight, high cost, low thermal conductivity and uneven temperature field in the thermal management of new energy batteries, resulting in poor thermal management performance.
A composite material was designed to ensure that the battery operates in the safe temperature range by adding boron nitride and expanded graphite in paraffin, combined with liquid silicone rubber and multi-layer graphene. .
It improves the thermal stability and cooling performance of new energy batteries, extends the service life of the battery, and effectively controls the temperature, avoiding battery overheating and leakage.
Smart Images

Figure CN119161737A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy batteries, and more specifically, to a composite material for thermal management of new energy batteries and a preparation method thereof. Background Art
[0002] In order to alleviate the increasingly serious environmental problems and energy crisis, new energy vehicles are gradually replacing traditional fuel vehicles due to their significant energy-saving and emission-reduction effects. New energy vehicles have lower costs and lower noise. Therefore, new energy vehicles have become one of the important development directions of the future automotive industry.
[0003] As the power source or main power source of new energy vehicles, new energy batteries mainly include lead-acid batteries, nickel-metal hydride batteries, lithium-ion batteries and fuel cells. Among them, lithium-ion batteries have the characteristics of high energy density, fast charging and long life and have been widely used. However, in practical applications, the performance of lithium-ion batteries is mainly affected by temperature. Low temperature will cause the battery capacity of lithium-ion batteries to decrease, while high temperature will cause heat accumulation, thereby reducing the battery life and even causing battery combustion or explosion. Therefore, in existing research, the temperature of new energy batteries will be adjusted through a battery thermal management system. The battery thermal management system is divided into air cooling system, liquid cooling system, phase change material cooling system and heat pipe cooling system according to different cooling media. Among them, the phase change material cooling system refers to cooling the battery pack through phase change materials. Phase change materials absorb or release a large amount of latent heat during the phase change process, thereby cooling the new energy battery. However, the existing phase change material cooling system has high weight and cost, low thermal conductivity and uneven temperature field, resulting in poor thermal management performance.
[0004] Therefore, there is an urgent need to study phase change materials with higher thermal conductivity for new energy batteries. Summary of the invention
[0005] The purpose of the present invention is to design and develop a composite material for thermal management of new energy batteries. The thermal conductivity of the composite material is improved by adding boron nitride and expanded graphite to paraffin. At the same time, liquid silicone rubber and multilayer graphene are combined to ensure the sealing performance of the battery.
[0006] The present invention also designs and develops a method for preparing a composite material for thermal management of new energy batteries. By adjusting the ratio of each component, the temperature control effect of the new energy battery is improved, ensuring that the battery operates in a safe temperature range, and increasing the service life of the battery.
[0007] The technical solution provided by the present invention is: A composite material for thermal management of new energy batteries, the composite material comprising paraffin wax, boron nitride, expanded graphite, AB two-component liquid silicone rubber and multilayer graphene, the mass ratio of the paraffin wax, boron nitride and AB two-component liquid silicone rubber is 9:1:9, the mass of the expanded graphite is 5-8% of the total mass of the paraffin wax and the boron nitride, and the mass of the multilayer graphene is 2% of the mass of the AB two-component liquid silicone rubber.
[0008] Preferably, the mass ratio of component A to component B of the AB two-component liquid silicone rubber is 1:1.
[0009] A method for preparing a composite material for thermal management of new energy batteries comprises the following steps: Step 1, heating the paraffin to melt and keep it in a molten state; Step 2: Add boron nitride to the melted paraffin and perform ultrasonic vibration for 30 minutes to obtain a mixed solution; Wherein, the mass ratio of paraffin wax to boron nitride is 9:1; Step 3: adding expanded graphite to the mixed solution, stirring for 1 to 2 hours, and cooling to room temperature to obtain an initial phase change material; Wherein, the added mass of the expanded graphite is 5-8% of the total mass of the mixed solution; Step 4: Add multilayer graphene to the AB two-component liquid silicone rubber and stir evenly, then add the initial phase change material, mix evenly, and cure to obtain a composite material for thermal management of new energy batteries; Among them, the mass ratio of AB two-component liquid silicone rubber to paraffin is 1:1.
[0010] Preferably, the step 1 is heated by a water bath, and the heating temperature is 70°C.
[0011] Preferably, the preparation of the expanded graphite comprises the following steps: Step 1, drying natural graphite in a vacuum drying oven at 60° C. for 16 h to obtain dry graphite; Step 2, placing the dry graphite in a muffle furnace and heating it to obtain expanded graphite; The heating temperature was 800° C., and the mass of the dried graphite was 0.5 g each time.
[0012] Preferably, the mass ratio of component A to component B of the AB two-component liquid silicone rubber is 1:1.
[0013] Preferably, the added mass of the multilayer graphene is 2% of the mass of the AB two-component liquid silicone rubber.
[0014] Preferably, the carbon content of the natural graphite in step 1 is greater than 99.99%.
[0015] Preferably, the particle size of the expanded graphite is 80 mesh and the expansion rate is 200-300 mL / g.
[0016] The beneficial effects of the present invention are: (1) The present invention designs and develops a composite material for thermal management of new energy batteries. The interior of boron nitride is filled with paraffin wax. Expanded graphite and paraffin wax are adsorbed on each other, thereby increasing the filling degree. Liquid silicone rubber and multilayer graphene are combined on the basis of the boron nitride layered structure to make the surface structure smooth, thereby ensuring the synergistic effect of thermal conductivity and ensuring that paraffin wax is not easy to leak during phase change, thereby improving the thermal conductivity effect.
[0017] (2) The preparation method of the composite material for thermal management of new energy batteries designed and developed by the present invention improves the temperature control effect of new energy batteries by adjusting the ratio of each component of the raw materials, ensures that the battery operates in a safe temperature range, and increases the service life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a SEM schematic diagram of the boron nitride of the present invention.
[0019] Figure 2 This is a SEM schematic diagram of the paraffin wax, boron nitride and expanded graphite mixed according to the present invention.
[0020] Figure 3 This is a SEM schematic diagram of the composite material of Example 1 of the present invention.
[0021] Figure 4 It is a curve diagram of the change of battery surface temperature of the composite materials of Examples 1-3 and Comparative Examples 1-3 of the present invention at an ambient temperature of 25° C. and a discharge rate of 4C.
[0022] Figure 5 It is a schematic diagram of the relationship curve between the temperature and leakage rate of the composite materials of Examples 1-3 and Comparative Examples 1-3 of the present invention. DETAILED DESCRIPTION
[0023] The present invention is further described in detail below so that those skilled in the art can implement it according to the description.
[0024] A composite material for thermal management of new energy batteries provided by the present invention comprises paraffin wax, boron nitride, expanded graphite, AB two-component liquid silicone rubber and multilayer graphene, wherein the mass ratio of the paraffin wax, boron nitride and AB two-component liquid silicone rubber is 9:1:9, the mass of the expanded graphite is 5-8% of the total mass of the paraffin wax and the boron nitride, and the mass of the multilayer graphene is 2% of the mass of the AB two-component liquid silicone rubber.
[0025] In this embodiment, the AB two-component liquid silicone rubber is HY-9310 liquid silicone rubber (SR) produced by Shenzhen Hongyejie Technology Co., Ltd.
[0026] The present invention also provides a method for preparing a composite material for thermal management of new energy batteries, which specifically comprises the following steps: Step 1, heating the paraffin to melt and keep it in a molten state; The paraffin wax can be heated by any heating method known in the art, such as water bath heating, oil bath heating, flat plate electric heating, etc. In this embodiment, the paraffin is heated by a water bath, and the water bath needs to be preheated before heating, the preheating temperature is 70° C., and the temperature is kept constant; Step 2, adding boron nitride to the melted paraffin, and ultrasonically shaking for 30 minutes to obtain a mixed solution; Wherein, the mass ratio of paraffin wax to boron nitride is 9:1; Step 3: adding expanded graphite to the mixed solution, stirring for 1 to 2 hours, and cooling to room temperature to obtain an initial phase change material; Wherein, the addition ratio of the expanded graphite is 5-8%; The preparation of the expanded graphite comprises the following steps: Step 1, drying natural graphite in a vacuum drying oven at 60° C. for 16 h to obtain dry graphite; Step 2, placing the dry graphite in a muffle furnace for high-temperature expansion to obtain expanded graphite; The heating temperature was 800° C., and the mass of the dried graphite was 0.5 g each time.
[0027] Step 4: Add multilayer graphene to the AB two-component liquid silicone rubber and stir evenly, then add the initial phase change material, mix evenly, and cure to obtain a composite material for thermal management of new energy batteries; Among them, the mass ratio of AB two-component liquid silicone rubber to paraffin is 1:1; The mass ratio of component A (silicone) to component B (curing agent) of the AB two-component liquid silicone rubber is 1:1; The added mass of the multilayer graphene is 2% of the mass of the AB two-component liquid silicone rubber; In this embodiment, the natural graphite is high-purity natural graphite with a carbon content greater than 99.99%. The particle size of the expanded graphite after expansion is 80 meshes, and the expansion rate is 200-300 mL / g.
[0028] Example 1 Preheat a water bath to 70°C and keep the temperature constant. Put 25g of paraffin wax into a beaker and put it into a water bath to melt and keep it in a molten state. Add boron nitride to the melted paraffin at a mass ratio of paraffin wax to boron nitride = 9:1. After ultrasonic oscillation for 30 minutes, add expanded graphite at a ratio of 5% of the total mass, stir for 1 hour, and cool to room temperature to obtain an initial phase change material. Add multilayer graphene accounting for 2% of its mass to the AB two-component liquid silicone rubber, stir evenly, then add the initial phase change material, mix quickly and evenly, and the stirring time should not be too long, which will cause curing. In this embodiment, the mixing time is 3 minutes, and the composite material for thermal management of new energy batteries is obtained by curing and molding.
[0029] Example 2 Preheat a water bath to 70°C and keep the temperature constant. Put 25g of paraffin wax into a beaker and put it into a water bath to melt and keep it in a molten state. Add boron nitride to the melted paraffin at a mass ratio of paraffin wax to boron nitride = 9:1. After ultrasonic oscillation for 30 minutes, add expanded graphite at a ratio of 6% of the total mass, stir for 1 hour, and cool to room temperature to obtain an initial phase change material. Add 2% of multilayer graphene by weight to the AB two-component liquid silicone rubber, stir evenly, then add the initial phase change material, stir quickly for 3 minutes to mix evenly, and cure to obtain a composite material for thermal management of new energy batteries.
[0030] Example 3 Preheat a water bath to 70°C and keep the temperature constant. Put 25g of paraffin wax into a beaker and put it into a water bath to melt and keep it in a molten state. Add boron nitride to the melted paraffin at a mass ratio of paraffin wax to boron nitride = 9:1. After ultrasonic oscillation for 30 minutes, add expanded graphite at a ratio of 8% of the total mass, stir for 2 hours, and cool to room temperature to obtain an initial phase change material. Add 2% of multilayer graphene by weight to the AB two-component liquid silicone rubber, stir evenly, then add the initial phase change material, stir quickly for 3 minutes to mix evenly, and cure to obtain a composite material for thermal management of new energy batteries.
[0031] Comparative Example 1 Preheat a water bath to 70°C and keep the temperature constant. Put 25g of paraffin wax into a beaker and put it into the water bath to melt and keep it in a molten state. Add expanded graphite to the melted paraffin at a mass ratio of 5%, stir for 1h, and cool to room temperature to obtain an initial phase change material. Add 2% multilayer graphene by weight to the AB two-component liquid silicone rubber, stir evenly, then add the initial phase change material, mix quickly and evenly, and do not stir for too long, otherwise it will solidify. In this embodiment, the mixing time is 3 minutes, and the composite material is obtained by solidification.
[0032] Comparative Example 2 Preheat a water bath to 70°C and keep the temperature constant. Put 25g of paraffin wax into a beaker and put it into a water bath to melt and keep it in a molten state. Add boron nitride to the melted paraffin at a mass ratio of paraffin wax to boron nitride = 9:1. After ultrasonic oscillation for 30 minutes, add expanded graphite at a ratio of 3% of the total mass, stir for 2 hours, and cool to room temperature to obtain an initial phase change material. Add 2% by weight of multilayer graphene to the AB two-component liquid silicone rubber, stir evenly, then add the initial phase change material, stir quickly for 3 minutes to mix evenly, and cure to obtain a composite material.
[0033] Comparative Example 3 Preheat a water bath to 70°C and keep the temperature constant. Put 25g of paraffin wax into a beaker and put it into a water bath to melt and keep it in a molten state. Add boron nitride to the melted paraffin at a mass ratio of paraffin wax to boron nitride = 9:1. After ultrasonic oscillation for 30 minutes, add expanded graphite at a ratio of 10% of the total mass, stir for 2 hours, and cool to room temperature to obtain an initial phase change material. Add 2% by weight of multilayer graphene to the AB two-component liquid silicone rubber, stir evenly, then add the initial phase change material, stir quickly for 3 minutes to mix evenly, and cure to obtain a composite material.
[0034] like Figure 1 As shown in FIG. 1 , it is a SEM schematic diagram of boron nitride. It can be seen that the structure of boron nitride is a sheet structure with multiple layers stacked together. Figure 2 As shown in FIG. 1 , it is a SEM schematic diagram of paraffin wax, boron nitride and expanded graphite mixed. The paraffin wax fills the interior of the boron nitride, and the expanded graphite and the paraffin wax adsorb each other, thereby increasing the filling degree. Figure 3 As shown, this is the composite material prepared in Example 1. It can be seen that the overall structure has both a layered structure and a smooth surface structure, which can not only ensure the synergistic effect of thermal conductivity, but also ensure that paraffin is not easy to leak during phase change, thereby improving the thermal conductivity effect.
[0035] like Figure 4As shown, the composite materials obtained in Examples 1-3 and Comparative Examples 1-3 are respectively coated on the outside of the same lithium-ion battery at an ambient temperature of 25°C and a battery surface temperature change curve at a discharge rate of 4C. At the same time, the lithium-ion battery is not coated in any way, and the single battery is also subjected to the same temperature test. The lithium-ion battery is a 18650 lithium iron phosphate battery. It can be seen from the figure that the single battery only dissipates heat through air, and the battery temperature shows a linear upward trend within 1000s. After 1000s, the temperature has reached above 65°C, exceeding the safe temperature range of the lithium-ion battery; while in Comparative Examples 1-3, the battery temperature is controlled, but after 600s, the temperature is basically above 40°C. In comparison, the composite materials of Examples 1-3 control the temperature of the lithium-ion battery within 40°C, and there is basically no sudden change in the temperature within 1200s, indicating that the composite materials of Examples 1-3 have better temperature control of the battery and are more stable.
[0036] like Figure 5 As shown, the leakage rate of the composite materials obtained in Examples 1-3 and Comparative Examples 1-3 was tested, all the composite materials were coated on the outside of the same lithium ion battery and put into a drying oven, and the temperature in the drying oven was maintained at 100°C, and the composite materials were taken out and weighed every 1 hour. It can be seen from the figure that the composite material without boron nitride has a poor effect in preventing lithium ion battery leakage, and the leakage is more than 2% after 6 hours, while the composite material of Comparative Example 2 reduces the leakage rate of the lithium ion battery, and it exceeds 1% after 5 hours. The leakage of the composite material of Comparative Example 3 is higher than that of Comparative Example 1. In comparison, the composite materials of Examples 1-3 protect the lithium ion battery better and basically do not leak, indicating that the packaging effect of the composite materials of Examples 1-3 is better.
[0037] The invention designs and develops a composite material for thermal management of new energy batteries, which improves the thermal stability and cooling performance of the batteries.
[0038] The invention designs and develops a method for preparing a composite material for thermal management of new energy batteries, which improves the temperature control effect of new energy batteries by adjusting the ratio of various components of the raw materials, ensures that the batteries work in a safe temperature range, and increases the service life of the batteries.
[0039] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the embodiments shown and described herein.
Claims
1. A composite material for thermal management of new energy batteries, characterized in that: The composite material includes paraffin wax, boron nitride, expanded graphite, AB two-component liquid silicone rubber and multilayer graphene, the mass ratio of the paraffin wax, boron nitride and AB two-component liquid silicone rubber is 9:1:9, the mass of the expanded graphite is 5-8% of the total mass of the paraffin wax and the boron nitride, and the mass of the multilayer graphene is 2% of the mass of the AB two-component liquid silicone rubber.
2. The composite material for thermal management of new energy batteries according to claim 1, characterized in that: The mass ratio of component A to component B of the AB two-component liquid silicone rubber is 1:
1.
3. A method for preparing a composite material for thermal management of new energy batteries, characterized in that: The steps include: Step 1, heating the paraffin to melt and keep it in a molten state; Step 2: Add boron nitride to the melted paraffin and perform ultrasonic vibration for 30 minutes to obtain a mixed solution; Wherein, the mass ratio of paraffin wax to boron nitride is 9:1; Step 3: adding expanded graphite to the mixed solution, stirring for 1 to 2 hours, and cooling to room temperature to obtain an initial phase change material; Wherein, the added mass of the expanded graphite is 5-8% of the total mass of the mixed solution; Step 4: Add multilayer graphene to the AB two-component liquid silicone rubber and stir evenly, then add the initial phase change material, mix evenly, and cure to obtain a composite material for thermal management of new energy batteries; Among them, the mass ratio of AB two-component liquid silicone rubber to paraffin is 1:
1.
4. The method for preparing a composite material for thermal management of new energy batteries according to claim 3, characterized in that: The step 1 is heated by a water bath, and the heating temperature is 70°C.
5. The method for preparing a composite material for thermal management of new energy batteries according to claim 4, characterized in that: The preparation of the expanded graphite comprises the following steps: Step 1, drying natural graphite in a vacuum drying oven at 60° C. for 16 h to obtain dry graphite; Step 2, placing the dry graphite in a muffle furnace and heating it to obtain expanded graphite; The heating temperature was 800° C., and the mass of the dried graphite was 0.5 g each time.
6. The method for preparing a composite material for thermal management of new energy batteries according to claim 5, characterized in that: The mass ratio of component A to component B of the AB two-component liquid silicone rubber is 1:
1.
7. The method for preparing a composite material for thermal management of new energy batteries according to claim 6, characterized in that: The added mass of the multilayer graphene is 2% of the mass of the AB two-component liquid silicone rubber.
8. The method for preparing a composite material for thermal management of new energy batteries according to claim 7, characterized in that: The natural graphite in step 1 has a carbon content greater than 99.99%.
9. The method for preparing a composite material for thermal management of new energy batteries according to claim 8, characterized in that: The particle size of the expanded graphite is 80 meshes, and the expansion rate is 200-300 mL / g.
Citation Information
Patent Citations
Preparation method of thermally conductive silica gel composite phase change material for battery thermal management system
CN106356588A
Phase-change heat storage silica gel and preparation method and application thereof
CN110317578A
High-thermal-conductivity phase-change organic silicon rubber and preparation method and application thereof
CN113956664A
Worm graphite packaged heat-conducting phase-change particle and thermal interface material and preparation method thereof
CN115584243A
